Correlative chemical and structural investigations of accelerated phase evolution in a nanocrystalline high entropy alloy. (1st July 2020) - Li, Y.J.; Kostka, A.; Savan, A.; Ludwig, A.
Graphical abstract: Abstract: Based on our recently-developed combinatorial processing platforms for accelerated investigations of phase evolution in multinary alloys, a novel correlative atom probe tomography and transmission electron microscopy approach is proposed to study phase stability in a nanocrystalline CrMnFeCoNi alloy. We observed that the material can decompose at 250 ° C for 5 h or 300 ° C for 1 h, having the same decomposed products as in its coarse-grained counterpart after annealing at 500 ° C for 500 days. A low apparent activation energy for the diffusion of Ni in the nanocrystalline alloy is derived and explains the fast kinetics of phase decomposition in nanocrystalline alloys.